Genomic and ancestral variations linked to the development of post-acute sequelae of SARS-CoV-2 infection in Indian populations - Shenoy, Pooja Umesh; Udupa, Hrushikesh; Ananthakrishnan, A. I.; Sunil, Punya; Sardarni, Urvinder Kaur; Kumar, Narendra; Acharya, Arpan; Byrareddy, Siddappa N.; Upadhyai, Priyanka; Das, Ranajit (Frontiers in Genetics, 2026)
BackgroundSusceptibility to infectious diseases is a result of complex interactions between genomic, environmental, and clinical factors. COVID-19 severity and post-acute sequelae of COVID-19 (PASC) vary widely among individuals, yet its genetic determinants remain underexplored in Indian populations. In this article, we undertake an exploratory analysis to investigate candidate genetic variants and biological pathways underlying the clinical outcomes in COVID-19 severity and PASC.MethodsSixty individuals with a history of COVID-19 were genotyped, and their data were supplemented with publicly available datasets from the Genome Asia 100K and Gujarat Biotechnology Research Centre. Two case–control genome-wide association study (GWAS) models were analyzed: (i) COVID-19 severity (mild/asymptomatic vs. severe) and (ii) an exploratory, hypothesis-generating GWAS for PASC (presence vs. absence of post-COVID-19 complications). Candidate genes identified here were further compared with RNA-sequencing datasets derived from brain and lung tissues of SARS-CoV-2-infected hamsters. The population-specific genetic risk for PASC was estimated using the polygenic risk score algorithm PRSice-2.ResultsGWAS identified candidate genes common to both COVID-19 severity and PASC, including CNTNAP2, WWOX, and ADAMTS17, which are implicated in extracellular matrix remodeling and neurological and cognitive development. We identified 806 candidate genes shared between the severity and PASC cohorts. Of these, 30 protein-coding genes were associated with neuropsychiatric disorders, and 23 were linked to cardiovascular conditions. Notably, CACNA1C, SLC8A1, GRK5, PDE4B, and LRRK2 were identified in both categories, suggesting potential convergence of molecular pathways underlying neurological and cardiovascular dysfunction. Integration with transcriptomic data reinforced the involvement of shared molecular pathways disrupted by SARS-CoV-2 infection. Polygenic risk analysis revealed significant population-specific variation in genetic predisposition to PASC.ConclusionGenetic susceptibility to severe COVID-19 and PASC in Indian populations appears to be linked to dysregulation of pathways central to cardiac and neurological function. These findings, derived from an exploratory PASC GWAS, provide preliminary insights into the molecular mechanisms that may underlie the post-viral sequelae. These emphasize the need for population-wide genomic studies to validate the candidate associations, better understand PASC risk, and facilitate the development of precision diagnostics and therapeutics.